Abscess and aneurysm: A case of tuberculous abscess causing an aortic pseudo-aneurysm - Anjalie Gulati, BS; Steven Esses, MD (Radiology Case Reports)
Thoracic aortic pseudoaneurysms are a rare but serious complication of infectious processes, often resulting from mycotic (infectious) aneurysms, occurring when the vessel wall is compromised by an infection, leading to the formation of a pseudoaneurysm [1]. Mycotic aneurysms typically result from bacteremia or fungemia, with common sources being infective endocarditis or other systemic infections. Tuberculosis, though a common infectious disease worldwide, is an unusual cause of aortic pseudoaneurysm formation. We present the case of a 26-year-old Asian male with a history of positive Quantiferon test, who presented with two weeks of back pain, hemoptysis, cough, night sweats, fever, and chills. CT imaging revealed a pseudoaneurysm at the T11-T12 level, associated with an epidural abscess, prevertebral rim-enhancing collection, and signs of osteomyelitis. The patient underwent endovascular repair of the aortic aneurysm, followed by drainage and biopsy of the epidural abscess and antibiotic therapy for the underlying infection. This case demonstrates the rare occurrence of a mycotic aneurysm caused by tuberculous infection, and the importance of early diagnosis and prompt surgical intervention to prevent catastrophic complications such as rupture, sepsis, or neurological impairment.